The epidemiology of anaphylaxis in Europe: a systematic review. Issue 11 (14th October 2013) - Panesar, S. S.; Javad, S.; de Silva, D.; Nwaru, B. I.; Hickstein, L.; Muraro, A.; Roberts, G.; Worm, M.; Bilò, M. B.; Cardona, V.; Dubois, A. E. J.; Dunn Galvin, A.; et al.
Abstract: Background: Anaphylaxis is an acute, potentially fatal, multi‐organ system, allergic reaction caused by the release of chemical mediators from mast cells and basophils. Uncertainty exists around epidemiological measures of incidence and prevalence, risk factors, risk of recurrence, and death due to anaphylaxis. This systematic review aimed to (1) understand and describe the epidemiology of anaphylaxis and (2) describe how these characteristics vary by person, place, and time. Methods: Using a highly sensitive search strategy, we identified systematic reviews of epidemiological studies, descriptive and analytical epidemiological investigations, and studies involving analysis of routine data. Results: Our searches identified a total of 5 843 potentially eligible studies, of which 49 satisfied our inclusion criteria. Of these, three were suitable for pooled estimates of prevalence. The incidence rates for all‐cause anaphylaxis ranged from 1.5 to 7.9 per 100 000 person‐years. These data indicated that an estimated 0.3% (95% CI 0.1–0.5) of the population experience anaphylaxis at some point in their lives. Food, drugs, stinging insects, and latex were the most commonly identified triggers. Conclusions: Anaphylaxis is a common problem, affecting an estimated 1 in 300 of the European population at some time in their lives. Future research needs to focus on better understanding of the trends across Europe and identifying those most likely to experience fatal reactions.